(3QSGdI ef eQGSdGJ CHh GdfLG SYhOs - (3CHh GdfLG SYhOs
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUdi Gddg Ydi SjOfG hfHjfG eMeO GdeUWai GdcQje CNhfG ai Gddg GdSdWGf GdPi CUdM Gddg Hg eG aSO ef CeQ GdOfjG hGdOjf CHh GdfLG SYhO GdeWGY CeG HYO abO Cfgi Edi MVQJfG GdYdjI HGddg s
(3BNQgG (B:s
(3hCfJe HMeO Gddg bO ecf Gddg dce ai GdCQV eJNdbjf HGdChWGf GdYQHjI heJeScjf HGdCMcGe GdTQYjI EfJgJ hHGdeMGSf EROgQJ HMeO Gddg hMSf Yhfg hUdi Gddg Ydi SjOfG eMeO fHjg hYHOg hYdi Bdg hUMHg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3fSNI ecQQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJGQjNs